PLANT AND LEARN EDUKASI BERKEBUN CABAI MELALUI PEMBELAJARAN TEMATIK BERBASIS LINGKUNGAN UNTUK ANAK USIA DINI - Eviani, Nur; Hayyati, Nur; Amanda, Kikan Tria; Lailasariyanti, Yennyka (Universitas katolik Musi Charitas, 2025)
Purpose: This community service activity aims to introduce early childhood learners to chili gardening through an environment based thematic learning approach. The program is designed to stimulate creativity, develop sensory and motor skills, and provide early education on simple gardening practices that can be applied in the home environment. Design Methodology Approach: The program was implemented at the official residence of KRPH Panceng, Gresik, and involved 12 early grade students from UPT SDN 322. Activities were conducted through thematic education using visual brochures, hands on chili planting practice, and interactive educational games such as Guess the Picture and Guess Who I Am. Evaluation was carried out through direct observation and simple question and answer sessions to assess student understanding and engagement. Findings: The results indicate that 66 percent of participants were able to restate the learning materials, follow instructions appropriately, and recognize new vocabulary related to gardening activities. High levels of enthusiasm and active participation were observed throughout the program. Practical Implications: This program effectively builds basic environmental awareness and gardening knowledge from an early age. The approach can be replicated in schools and community settings as part of thematic learning to strengthen environmental care character development. Originality Value: This program integrates environmental education and practical gardening activities within an enjoyable thematic learning framework. The initiative contributes to character education and supports food security awareness through a contextual and applicable educational approach.